Wreck Removal and the Nairobi Convention—a Movement Toward a Unified Framework? - Kern, Jhonnie M. (Frontiers in Marine Science, 2016)
The Nairobi International Convention on the Removal of Wrecks came into force on the 14 of April 2015 and provides a framework for wreck removal. Three central questions arise when dealing with shipwrecks; Who is responsible? What measures can and are to be taken based on such a responsibility? And lastly; how can the responsibility be enforced? The Nairobi Convention on the Removal of Wrecks addresses these questions. The registered owner of a ship bears strict liability according to the convention but can be exonerated by certain limited defenses. Measures that are to be taken include locating, marking and subsequently removing the wreck. The onus to remove the wreck is on the registered owner, but there are also options available for the State affected by the wreck should the registered owner not cooperate or be unable to contact. Finally the convention strives to ensure enforceability by compulsory insurance for ships, wherever registered, with a gross tonnage of 300 tons and above calling any port or offshore facility in a State Party. The convention also enables an Affected State to claim the insurer directly. This article will analyze the convention by the use of the convention text, its preparatory works and legal writing. The article suggests that even though the convention provides a unified framework for wreck removal, it has inclusions that may actually inhibit harmonization. The convention is also in part unclear and ambiguous. Despite this the article concludes in the convention being a natural step forward in unifying the regulation of wrecks and providing a platform to deal with wreck removal in the future.